Comparative Efficacy of Multiple Therapies for the Treatment of Patients With Subthreshold Depression: A Systematic Review and Network Meta-Analysis - Jiang, Xiumin; Luo, Yongxin; Chen, Yiwen; Yan, Jinglan; Xia, Yucen; Yao, Lin; Wang, Xiaotong; He, Su; Wang, Feixue; Wang, Taiyi; Chen, Yongjun (Frontiers in Behavioral Neuroscience, 2021)
Background: Subthreshold depression (SD) is considered to be the precursor stage of major depression, which is correlated with functional impairment and increased suicide rate. Although there are multiple therapies for the treatment of SD, the comparison and efficacy of various methods has yet to be evaluated. This study aimed to evaluate the efficacy of different therapies by performing a Bayesian network meta-analysis. Methods: We searched eight databases on April 3, 2021. Center for Epidemiologic Studies Depression scale (CES-D), Beck Depression Inventory scale (BDI), the Patient Health Questionnaire-9 (PHQ-9), and the Kessler Screening Scale for Psychological Distress (K-6) were used as efficacy outcomes. This Bayesian network meta-analysis used a fixed-effects model. Findings: Twenty-one randomized controlled trials involving 5062 participants were included in this study. The results suggested that electroacupuncture (MD -12.00, 95% CrI -15.00, -10.00), conventional acupuncture plus wheat-grain moxibustion (MD -9.70, 95% CrI -14.00, -5.30) and the Chinese traditional peripateticism pill plus group counseling (MD -9.00, 95% CrI -11.00, -6.70) had better efficacy than the control group (CG) in improving CES-D. For BDI outcome, bright light therapy (MD -9.70, 95% CrI -13.00, -6.00), behavioral activation program (MD -5.70, 95% CrI -6.10, -5.40) and dim light therapy (MD -6.30, 95% CrI -10.00, -2.20) were better than the CG. Tai chi (MD -3.00, 95% CrI -4.00, -2.00) was better than CG for PHQ-9 outcomes. Telephone-based cognitive behavioral treatment (MD -2.50 95% CrI -2.70, -2.30) was better than the CG for K-6 scores. Conclusion: Our results suggest that electroacupuncture or bright light therapy appear to be the better choices in the treatment of SD. This study provide new insights into clinical treatment selection and may aid the development of guidelines for the management of SD.